2013
DOI: 10.21106/ijma.15
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Tract Infections and Treatment Seeking Behavior among Married Adolescent Women 15-19 Years in India

Abstract: Background:India is home to the highest number of adolescents in the world. Adolescents in India suffer from lack of knowledge and empowerment to make informed sexual and reproductive health decisions. This paper analyses the prevalence of reproductive tract infections and sexually transmitted infections (RTI/STI) and treatment seeking behavior among married adolescent women in India aged 15-19 years.Methods:Data from the District Level Household Survey (DLHS, 2007-08) of India were used. The prevalence of RTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
(15 reference statements)
8
17
1
Order By: Relevance
“…Additionally, Hashemian, et al (2015) Indian who declared that majority of women with symptoms related to reproductive tract infections were positive for reproductive infections but were not taking medical treatments. Also, our study disagree with (Prusty, et al, 2013) their study about knowledge and health seeking behaviors among women of reproductive age group they claimed that the treatment seeking was also poor among the reproductive age group. It could be due to the difference in subject and time of data collection.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, Hashemian, et al (2015) Indian who declared that majority of women with symptoms related to reproductive tract infections were positive for reproductive infections but were not taking medical treatments. Also, our study disagree with (Prusty, et al, 2013) their study about knowledge and health seeking behaviors among women of reproductive age group they claimed that the treatment seeking was also poor among the reproductive age group. It could be due to the difference in subject and time of data collection.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the findings of the current study are in line with findings of the study conducted by Sabarwal et al, 16 who studied "Treatment seeking for symptoms of RTIs among young women" found that, the treatment seeking for any RTI infection was poor and 66% of unmarried women had not sought any treatment for their symptoms. Correspondingly, the finding by Prusty & Unisa, 17 who studied "RTIs and treatmentseeking behavior among married female adolescents in India", found that, treatmentseeking behavior among female adolescents is poor. The findings of current study interpreted that in spite the recurrence of infection per year many times for female students they didn't seek treatment due to many barriers.…”
Section: Discussionmentioning
confidence: 95%
“…A study conducted in urban slums of Mumbai, India revealed that major predictors of both symptoms of reproductive infections and treatment seeking behavior from multivariate analysis are age, education, wealth, region and awareness about RTIs/STIs. 15 It is a common problem in India for women in the reproductive age group to suffer from reproductive illnesses and not to seek care. This paper is an attempt to assess treatment seeking behavior among ever married women of the reproductive age group who had reported STIs/RTIs symptoms at the STI/RTI Clinic of Urban Health Centre, Shivaji Nagar, Govandi, Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%